Pemantauan Populasi Imago Spodoptera litura dan Helicoverpa armigera Menggunakan Perangkap Seks Feromon - GUSTI NGURAH GEDE DHARMA PUTRA PUTRA; I PUTU SUDIARTA; I PUTU DHARMA; KETUT SUMIARTHA; R. SRINIVASAN (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2013)
ABSTRACT Monitoring of Imago of Spodoptera litura and Helicoverpa armigera Using Sex Pheromone Trap The utilization of sex pheromone to control insect pest is one of advance technology. The sex pheromone is one method to control insect pests for support food security. In other to know the ability of sex pheromone to trap insect the monitoring of insect using sex pheromone is needed. The lure of sex pheromone, glue, and box trap were imported from AVRDC-The World Vegetable Center. Sex pheromone trap is putted on the vegetable area in Bali, the locations including Sandan, Kembang Merta, Candi Kuning (Tabanan Regence) and Pancasari (Buleleng Regence). On each location trap was placed with two replications. Data collection was conducted every week, on 3rd week observation the imago/moth population is completely reduce. Therefore the trap was replaced for the new trap. That mean the observation was conducted 3 times per experiment (Observation 1,2,3). In this case the experiments were done 2 times (Experiment 1 and 2). The identification of imago was base on the morphological method. The imago was accounted for data collection. The decrease of population of Spodoptera litura and Helicoverpa armigera after 3 week observation is possible caused by the ability of pheromone active ingredient is also decrease. The distribution of imago S. litura and H. armigera are same for all locations. However the total population of S. litura and H. armigera is different. The population of S. litura was very high in all locations around 51-107. However the population of H. armigera was generally low except in Sandan Tabanan (70). In Pacasari the population of H. armigera was lowest around 14-15. The differentiation of imago S. litura and H. armigera were possible influenced by the host plant, altitude and also climate conditions. Key worlds: sex pheromone, Spodotera litura, Helicoverpa armigira